Does human development policy matter for economic growth? evidence from Indian states - Pradhan, Jaya Prakash (2002)
For explaining growth differentials across the countries, recent growth literature is increasingly relying on the process of human capital accumulation along with the traditional factors like labour and non-human capital. This study has investigated the role of human development policy on the economic growth of Indian states for the period 1980-97. Evidences suggest that the human development position of the states is strongly determined by the human development policy pursued. Panel data evidence investigating the growth impact of human development policy found that economic growth significantly depends upon the human development policy. It confirmed that the government allocation for education is critical for economic development. However, per capita health expenditure does not posses any significant growth impact. - Reproduced.
Keywords: Economic growth